The Ability of Kindergarten Teacher to Use Information and Communication Technology - Adhawiyah, Rabiatul; Salehuddin, Mohammad Salehuddin (Psikoborneo: Jurnal Ilmiah Psikologi, 2023)
In the 21st century, teachers are required to have the characteristics of cooperation, creativity, critical thinking, and communication. This demand needs to be supported by the ability to use ICT (information and communication technology) for kindergarten teachers who play a role in educating and educating students well according to the times, but there are still teachers who do not understand and do not have ICT skills. This study aims to describe the ability of kindergarten teachers to use ICT. The method used is descriptive quantitative with data collection using surveys. The research subjects were 42 teachers who participated with incidental sampling technique. The results of this study indicate that as many as 26.2% of teachers can use ICT at a very high level. Furthermore, the results of the study were dominated by 38.1% of teachers having high ICT skills, followed by 31% of teachers having moderate ICT skills. However, there are still 4.8% of teachers who have low ability to use ICT.Pada abad 21 ini guru dituntut untuk memiliki karakteristik kerja sama, kreatif, berfikir kritis, dan komunikasi. Tuntutan ini perlu ditunjang oleh kemampuan menggunakan ICT (information and communication technology) pada guru Taman Kanak-Kanak yang berperan mendidik dan mencerdaskan anak didik secara baik sesuai perkembangan jaman, namun kenyataannya masih terdapat guru yang belum memahami dan belum memiliki kemampuan ICT. Penelitian ini bertujuan untuk mendeskripsikan kemampuan guru Taman Kanak-Kanak menggunakan ICT. Metode yang digunakan adalah kuantitatif deskriptif dengan pengumpulan data menggunakan survei. Subjek penelitian sebanyak 42 guru yang berpartisipasi dengan teknik insidental sampling. Hasil dari penelitian ini diketahui bahwa sebanyak 26,2% guru memiliki kemampuan menggunakan ICT pada tingkat sangat tinggi. Selanjutnya hasil penelitian didominasi dengan 38,1% guru memiliki kemampuan menggunakan ICT yang tinggi, kemudian disusul dengan 31% guru memiliki kemampuan ICT dalam tingkatan sedang. Namun masih ada 4,8% guru memiliki kemampuan menggunakan ICT yang rendah.